Exogenous Fecal Microbial Transplantation Alters Fearfulness, Intestinal Morphology, and Gut Microbiota in Broilers - Yan, Chao; Xiao, Jinlong; Li, Zhiwei; Liu, Hao; Zhao, Xinjie; Liu, Jian; Chen, Siyu; Zhao, Xingbo (Frontiers in Veterinary Science, 2021)
Fecal microbiota transplantation (FMT) documented transplanting a donor fecal sample to a receipt individual for a desired physiologic effect. However, whether the gut microbiota construction, intestinal maturation, and behavioral plasticity are modulated by FMT during the early life of broilers is waiting for verification. To evaluate the role of transfer of fecal microbiota from aged broilers donor (BD) to another individual, 96 birds were equally divided into a check (CK, control) group and a broiler recipient (BR) group. FMT was conducted daily from 5 to 12 days of age to determine the future impact on body weight, behavior, intestinal development, and gut microbiota. Results indicated that fearfulness in the CK group was higher than the BR group in both the behavioral tests (p < 0.05). The muscularis mucosa, thickness of muscle layer, and thickness of serous membrane layer in the BR group were higher compared with those of the CK group in the jejunum (p < 0.05). In the gut microbiota, Shannon diversity showed no difference, while beta diversity presented a difference in principal coordination analysis (PCoA) between the CK and BR groups. At the phylum level, the relative abundance of Lentisphaerae in the CK group was lower than the BR (p = 0.052) and BD (p = 0.054) groups. The relative abundance of Tenericutes in the BD group was higher than that in the CK and BR groups (p < 0.05). At the genus level, Megamonas in the CK group was higher than the BR (p = 0.06) and BD (p < 0.05) groups. In the BR group, the functional capabilities of microbial communities analyzed by the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway were increased in the glutamatergic synapse and N-glycan biosynthesis pathways in comparison with the CK and BD groups (p < 0.05). Some characteristics of gut microbiota in the donor chickens could be transferred to recipient chickens by FMT. In conclusion, exogenous FMT as a probiotic-like administration might be an efficient way to improve the physiology and behavior of chickens. Notably, the role of microbiota for various individuals and periods remains undefined, and the mechanism of microbiota on behaviors still needs further investigation.